Evaluation of Menala River Water Quality Based on Benthic Macroinvertebrate as Bioindicator to Support Tourism in Sumbawa Island, Indonesia - Sany, Zainul Muttaqin; Arisoesilaningsih, Endang; Retnaningdyah, Catur (Graduate School, Universitas Brawijaya, 2023)
The aquatic ecosystem in the Menala River has been degraded due to anthropogenic activities. The purpose of this study was to evaluate the water quality in the Menala River based on water physicochemical and benthic macroinvertebrates as bioindicators. Water quality was evaluated at seven stations based on anthropogenic activities in the surrounding. The physicochemical parameters measured included water temperature, turbidity, electrical conductivity, pH, DO, TDS, BOD, nitrate, and total phosphate. Benthic macroinvertebrate data were used to determine the importance value index (IVI), Shannon-Wiener diversity index (H'), evenness index (E), Simpson dominance index (C), the average score per taxon index (ASPT), and family biotic index (FBI). The data were analyzed by one-way ANOVA, biplot, and correlation test using PCA. The research result indicated that the concentration of DO (5.97 – 11.7 mg.L-1) at each station only fulfilled in class 3 of water quality, BOD (2.83 – 4.03 mg.L-1) in class 2, and Total phosphate (0.03 – 0.23 mg.L-1) only meets class 3. Based on the H', FBI, and ASPT index, the first station was categorized as clean water, the second to fourth stations were categorized as good to fairly poor, and the fifth to seventh stations were categorized as lightly polluted to probable severe pollution. Keywords: Benthic Macroinvertebrates, Menala River, physicochemical parameters, water quality.